(untitled) (Journal of Misan Researches, 2024)
The research aims to know the reality of the geographical distribution of private schools in the city of Amara for the academic year (2022-2023), and the extent of their efficiency and role in contributing to addressing weaknesses in government education and knowing their distribution pattern, as well as knowing the suitability of the spatial distribution of private education institutions in the city. The research study revealed that there are (38) private educational institutions, which included (primary and secondary schools), concentrated in specific residential neighborhoods in the study area, distributed among (8) residential neighborhoods out of (67) residential neighborhoods in the city. The neighborhood was ( Awashah) has acquired the largest number of private schools, as their number reached (18) primary and secondary private schools, while the number of students reached (8535) students in primary school, in which the number of male students exceeded the number of female students by (6262) students compared to (2273). Female students, while its share of teachers was (613) male and female teachers, in which the number of female teachers outnumbered male teachers by (330) schools compared to (283) male teachers. The study was based on using some statistical methods represented by geographic information systems (GIS) in measuring the efficiency of the reality of the spatial distribution of schools. National primary and secondary schools, represented by the nearest neighbor method, and population projections.